2015
DOI: 10.1093/jxb/erv246
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping of deep rooting by linkage and association analysis in rice

Abstract: HighlightMajor quantitative trait loci (QTLs) of rice deep rooting were identified by combined linkage-based and linage disequilibrium-based QTL mapping in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 58 publications
(71 reference statements)
3
82
0
2
Order By: Relevance
“…This population has previously been used in GWAS for mesocotyl elongation and ratio of deep rooting (Lou et al, 2015; Wu et al, 2015). All accessions were tested under two water regimes: well watered and drought stress, in a drought resistance screening facility (Luo, 2010) at the Baihe Experimental Station of the Shanghai Agrobiological Gene Center (31°15′N, 121°10′E, 4 m altitude) in 2011 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…This population has previously been used in GWAS for mesocotyl elongation and ratio of deep rooting (Lou et al, 2015; Wu et al, 2015). All accessions were tested under two water regimes: well watered and drought stress, in a drought resistance screening facility (Luo, 2010) at the Baihe Experimental Station of the Shanghai Agrobiological Gene Center (31°15′N, 121°10′E, 4 m altitude) in 2011 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, another QTL was identified (DRO3) that affects root growth angle in a DRO1-dependent manner (Uga et al, 2015). Additional QTL and genomewide association studies in rice revealed further QTLs for deeper root growth under water-deficit conditions (Courtois et al, 2009;Lou et al, 2015;Wade et al, 2015).…”
Section: Growth Direction Is Determined Locally By Water Availabilitymentioning
confidence: 99%
“…A plant with improved drought-avoidance might utilize more water via a well-developed root system, while a plant with improved drought-tolerance maintains its basic life activities even when dehydrated (Blum, 2005; Luo, 2010). Drought-avoidance via enlargement of the root system plays a primary role in plant responses to drought and the molecular basis for this has been studied and applied in the breeding of drought-resistant cultivars (Pietta, 2000; Uga et al, 2013; Lou et al, 2015). Drought-tolerance plays an important role during the later stage of drought and has great potential to enhance drought-resistance.…”
Section: Introductionmentioning
confidence: 99%